Hubungan antara Self-Efficacy dengan Student Engagement pada Siswa MAN Pinrang - Amirah Ansyar; Dian Novita Siswanti; Nur Akmal (CV. Ulil Albab Corp, 2023)
The progress of a country can be seen in the quality of education in that country. Active involvement of students in the school environment is very important. Active student involvement is called student engagement. Low student engagement will have an impact on low learning achievement and are more likely to experience frustration and receive negative responses from the teacher. Student engagement in students is influenced by many things, one of the factors of individual factors is that students must have self-efficacy. The purpose of this study was to determine the relationship between self-efficacy and student engagement in MAN Pinrang students. This research uses quantitative methods. Respondents in this study were 234 students who were obtained using random sampling techniques. This study was measured using a scale of self-efficacy and student engagement. The analysis used in this study is the Spearman Rho correlation with the help of SPSS 25.0 for windows. The results of this study indicate that the significant value is p = 0.000 (p <0.05) and the correlation coefficient is r = 0.406. Thus there is a positive relationship between selfefficacy and student engagement. A positive r value means that the higher the selfefficacy, the higher the student engagement